Psychometric properties of Global Transformational Leadership Scale: Lithuanian version - Stelmokienė, Aurelija; Endriulaitienė, Auksė (Psichologija, 2009)
Nowadays, leadership is seen as a research object related to a successful functioning of a modern organization. Transformational leadership is valued as most appropriate in today’s changing business world. But practitioners and researchers are lacking a broadly applicable, concise instrument which would also be reliable and valid to assess leaders’ transformational leadership skills. So, this research has been targeted to evaluate the psychometric properties (reliability and validity) of the Global Transformational Leadership scale Lithuanian version. The research involved 550 Lithuanian employees from various organizations; 112 respondents participated in the first and 438 respondents in the second stage of the research. All participants filled up a questionnaire consisting of the Global Transformational Leadership scale (Carless et al., 2000) and socio-demographic questions. Questions about job satisfaction (Shim et al., 2002), intentions to leave (Meyer and Tett, 1993), N. F. Mott’s proposed situations to evaluate management effectiveness (quoted after Chauhan et al., 2005) and Transformational Leadership Behavior Inventory (Podsakoff et al., 1990) were added to the questionnaire only in the second stage. The results have shown that the Global Transformational Leadership scale is highly reliable (Cronbach α = 0.925). Besides, the stability of the test–retest results (r = 0.868; p < 0.01; t = 0.921; p > 0.05) was an important feature of this scale. Exploratoryand confirmatory factor analyses used in studying the content validity showed that all seven items of the scale explained one factor – transformational leadership. Construct validity was confirmed by strong correlations (r = 0.815; p < 0.01) between the Global Transformational Leadership scale and the Transformational Leadership Behavior Inventory and by proven relations between transformational leadership and subordinates’ higher job satisfaction, lower turnover intentions, and better evaluations of management effectiveness. Thus, the Global Transformational Leadership scale can be characterized as an instrument with appropriate psychometric properties for individual and group analyses for the purpose of research and practice.
Keywords: transformational leadership; reliability and validity of Global Transformational Leadership scale